Parental Involvement in Follow – Up Learning Activities Relates to the Children’s English Language Skills Among Grade III pupils in the District of Castillejos, Division of Zambales, SY 2015 – 2016 - Corcoro, Lesley – Anne R. (Future Science / FSH-PH Publications, 2025)
The objective of the study was to ascertain the relationship between Grade III students' English language proficiency and parental participation in follow-up learning activities in the District of Castillejos, Division of Zambales, during the school year 2015–2016. The questionnaire was the primary tool used to collect data from 150 parent respondents in this study, which used a descriptive research design. According to the survey, the average parent-respondent is a housekeeper, a high school graduate with an income below the poverty line, and a member of a household consisting of three to five people. It is determined that parental participation in follow-up learning activities is